2015
DOI: 10.1093/ije/dyv146
|View full text |Cite
|
Sign up to set email alerts
|

Low frequency of cigarette smoking and the risk of head and neck cancer in the INHANCE consortium pooled analysis

Abstract: Our results suggest a public health message that low frequency of cigarette consumption contributes to the development of HNC. However, smoking duration seems to play at least an equal or a stronger role in the development of HNC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
43
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 13 publications
6
43
0
Order By: Relevance
“…Nevertheless, analogous findings to those in our study were observed in a recent case-control consortium study of head and neck cancer. 16 In this case-control study, participants who had averaged smoking of fewer than 0 to 3, more than 3 to 5, and more than 5 to 10 CPD over their lifetime had higher odds of head and neck cancer compared with never smokers.…”
Section: Discussionmentioning
confidence: 85%
“…Nevertheless, analogous findings to those in our study were observed in a recent case-control consortium study of head and neck cancer. 16 In this case-control study, participants who had averaged smoking of fewer than 0 to 3, more than 3 to 5, and more than 5 to 10 CPD over their lifetime had higher odds of head and neck cancer compared with never smokers.…”
Section: Discussionmentioning
confidence: 85%
“…However, it is possible that differences between HPV positive and HPV negative HNSCCs may be undervalued due to the lack of data regarding cumulative doses of tobacco and alcohol exposure, as also reported elsewhere [Gillison et al, ]. It has been reported that both tobacco doses and smoking duration are linked to the development of HNSCC [Berthiller et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Just a few studies to date have examined associations of low‐intensity smoking with cancer. Results from these studies are generally consistent with our findings, observing higher risk of cancers, such as lung and head and neck cancers, among those who smoked 1–10 CPD . Data on disease risks among nondaily smokers are even more limited.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have directly examined the health effects of long‐term low‐intensity smoking. Several studies have shown an increased risk of tobacco‐related cancer, but these studies have largely been unable to distinguish those who smoked at low‐intensity over their lifetime from those who smoked much more earlier in life …”
mentioning
confidence: 99%
See 1 more Smart Citation